Políticas públicas e juventude no espaço rural: assentamento Sepé Tiarajú - Serra Azul/SP - Mendes, Benedita da Guia Ferreira (2011)
The debate about the youth in the last decades has increasingly boosted the inclusion of this topic in the country political agenda as well as it has reinforced the need of understanding that the Brazilian youth is not homogeneous and it lacks further development in the social, cultural, and economic sectors of specific policies to that category. In that context, the Brazilian rural youth present themselves as a distant and invisible category from the urban youth. Besides the invisibility of the agrarian reform subjects, concerning the concrete needs and problems that involve them, there is also a distancing from the public policies in the agrarian reform settlements. Thus, the present research aimed to identify the public policies formulated to the rural youth within the State, and understand the impacts of their deployment in the youngsters lives in Sepé Tiarajú settlement, which is located in Serra Azul/SP. Based on conducting a bibliographical research, semi-structured interviews, and direct observations, it was possible to notice that the youth in the settlement are invisible to those involved in the organizational process, as well as the existing public policies are distanced from the reality of the settlement. Although the settlements are near the cities, the reality of rural settlements has its own peculiarities regarding its organization and relationship to the existing social movements in those spaces. Education, work, and leisure-time activities are among the issues that most concern the youth and their families.